Response to the Article: “Primary Aldosteronism: Are We Missing the Wood for the Trees?” - Piaditis, G.; Pappa, T.; Markou, A.; Gouli, A.; Papanastasiou, L.; Kaltsas, G. (Hormone and Metabolic Research, 2012)
This letter is a short response to Dr Funder’s recent commentary on primary aldosteronism under the title “Primary aldosteronism: are we missing the wood for the trees?”. We briefly discuss recent data from our department on autonomous aldosterone secretion (AAS) and the efficacy of mineralocorticoid receptor antagonists in a group of patients with AAS, that would otherwise remain undiagnosed.